Homo-aro-cholestane, furostane and spirostane saponins from the tubers of Ophiopogon japonicus. (April 2017) - Wang, Lun; Jiang, Xi-Lan; Zhang, Wen-Ming; Li, Fu; Khan, Ashfaq-Ahmad; Liu, Xin; Yu, Kai; Wang, Ming-Kui
Abstract: Phytochemical investigation of the tubers of Ophiopogon japonicus led to the isolation of five previously undescribed steroidal saponins, ophiojaponins A–E, together with twelve known ones. The structures of these isolated compounds were elucidated by detailed spectroscopic analyses and chemical methods. Ophiojaponins A–C are rare naturally occurring C29 steroidal glycosides possessing a homo-cholestane skeleton with an aromatized ring E. Ruscogenin 1- O - α -L-rhamnopyranosyl-(1 → 2)-4- O -sulfo- β -D-fucopyranosido-3- O - β -D-glucopyranoside was isolated as single component and its full spectroscopic data was reported for the first time. The isolated steroidal saponins were evaluated for their cytotoxicities against two human tumor cell lines MG-63 and SNU387. Among them, five known spirostane-type glycosides showed cytotoxic activity against both MG-63 and SNU387 cell lines with IC50 values ranging from 0.76 to 27.0 μM. Graphical abstract: Seventeen steroidal saponins, including five previously unreported, were isolated from the tubers of Ophiopogon japonicus. The isolates were evaluated for their cytotoxicities against two human tumor cell lines. Highlights: Five previously undescribed steroidal saponins were characterized from Ophiopogon japonicus. Three of these compounds are rare naturally occurring C29 steroidal glycosides. Cytotoxic activities of isolated compounds were tested on two human cancer cell lines.